Changes of phosphorus, 210Po and 210Pb in water column at Mersing River, Johor - Saili, N.A.B; Mohamed, C.A.R (University Kebangsaan Malaysia, 2012)
The studies on natural radionuclides such as 210Po and 210Pb with the concentration of phosphorus in water column were carried out in Mersing River, Johor. There were 16 water samples were collected from nine stations during Mersing Expedition 2010 on the 4th July 2010. The samples were treated by using sequential extraction and counted using the gross alpha-beta counting system (Tennelec model 5 XLB low background gas-flowing anti-coincidence alpha-beta counter) for 210Pb and alpha spectrometry counting system (Canberra model Alpha Analyst Spectroscopy system with a silicon-surface barrier detector) for 210Po. The 210Po and 210Pb activities were varied between 0.755 to 2.238 mBq/L and 0.1555-1.598 mBq/L. While the phosphorus concentrations include TDP, SRP and DOP were in the range of 6.058 to 23.312 μg/L, 2.237 to 13.419 μg/L and 0.466 to 16.097 μg/L. Statistically, the activities of 210Po were positively correlated with TDP. In this study, the highest distribution of phosphorus and 210Po were found at Station 5 which located at boats jetty and very close to Mersing Town area while 210Pb was found at Station 1.